A voz calada na ponta da linha: o pesar vicário de bombeiros militares, sob a perspectiva do senso de coerência - Comaru, Claudia Marques (2021)
Military firefighters on the frontline work under the risk of death and deal with the emotional impact of contact with the affected people, affected people's families, and the affected community. The vicarious grief can be experienced through a sense of loss of a bond, even in the specific context of a single occurrence. This research aimed to understand the vicarious grief of military firefighters, in the light of the sense of coherence construction, which assesses the following aspects: meaning, understanding and managing in life experience. The method adopted was of a blended nature. The quantitative analysis described sociodemographic and labor information from 121 participants, as well as responses to the Life Orientation scale, which measures the sense of coherence construct (SOC-13), components of a questionnaire which was made available online. The qualitative analysis included semi-structured interviews, conducted with ten firefighters who work on the frontline in the state of São Paulo, who answered the questionnaire. This study necessarily requires that specific actions, regarding vicarious grief in the work process of firefighters, are developed to attend the part of the population that needs this service. It is necessary to expand the existing mental health structure in the institution, along with the capillarization of attention to the sensitive content of the work. The analysis of vicarious grief, from the perspective of the sense of coherence construction, pointed to the relevance of the following dimensions: understanding, management and meaning in understanding the emotional experience of work, which can support the construction and evaluation of mental health promotion and care strategies of military firefighters. Future studies, which use the qualitative method with the population of Brazilian firefighters, can add more meanings to the experience of operational work in the Latin American context